The current situation and future trends of sport science and technology in the "technology-empowered olympics" after the Beijing winter olympics - Wu, X.; Yuan, T.; Tang, C. (Advances in Social Science, Education and Humanities Research, 2023)
The purpose of this paper is to scientifically summarize the development status of the Winter Olympics, inherit and carry forward the scientific and technological heritage of the "Scientific and Technological Olympics", and conduct targeted research and discussion on the future development trend of sports science and technology. The study systematically discusses the development status, science and technology, and technological heritage of the Beijing Winter Olympics, and explores and interprets the connotation and significance of the "Science and Technology Olympics". Behind the competition of Olympic Games is the competition of science and technology, the history of 100 years of Olympic Games is also the history of sports science and technology development, "science and technology" and "Olympic Games" promote each other and mutually beneficial symbiosis; the scientific and technological Olympics have Chinese characteristics and Chinese wisdom, and the innovation of sports science and technology will play an important role in digital sports, intelligent sports and sports limit breakthrough. Sports technology innovation will play an important role in digital sports, intelligent sports and sports limit breakthrough; Technology Olympics will certainly help intelligent training venues, intelligent equipment, sports data, championship models, electronic judges, viewing experience and Olympic preparation. This shows that under the background of China`s "national system", applying the latest science and technology to sports practice, insisting on independent science and technology innovation, and vigorously developing the road of science and technology for athletics and mass sports can better carry forward the "spirit of Beijing Winter Olympics" and continue to bring the advanced technology of "Science and Technology Olympics" to the world. The advanced concept of "Science and Technology Olympics" will be carried forward.